Hemithoracic radiation therapy after extrapleural pneumonectomy for malignant pleural mesothelioma: Toxicity and outcomes at an Australian institution. Issue 3 (6th March 2015) - Bece, Andrej; Tin, Mo Mo; Martin, Darren; Lin, Robert; McLean, Jocelyn; McCaughan, Brian
Abstract Introduction We aim to report the outcome of patients with malignant pleural mesothelioma who underwent extrapleural pneumonectomy (EPP) and adjuvant hemithoracic radiotherapy with or without chemotherapy at a single Australian institution. Method Between July 2004 and March 2013, 53 patients were referred for radiation treatment following EPP, of whom 49 were suitable for adjuvant treatment. Radiation treatment initially involved a 3D conformal, mixed electron/photon technique, delivering 45–50.4 Gy in 25–28 fractions (31 patients) and subsequently a nine‐field intensity‐modulated radiotherapy technique, delivering 50.4–54 Gy in 28–30 fractions (18 patients). Fifty‐five per cent of patients also received pre‐operative chemotherapy. We assessed toxicity, disease‐specific and overall survival in patients who commenced radiation treatment. Results Forty‐one patients (84%) completed treatment as prescribed. Six patients stopped prematurely due to toxicity, and two with disease progression. Most patients discontinuing due to toxicity received over 90% of the prescribed dose. Common acute toxicities included nausea, fatigue, anorexia and dermatitis. Severe early toxicities were rare. Late toxicities were uncommon, with the exception of a persistent elevation in liver enzymes in those with right‐sided disease. Neither clinical hepatitis nor radiation pneumonitis was documented. With a median follow up of 18.7 months, median disease‐free and overall survival were 21.6 and 30.5 months, respectively, and 2‐year overall survival was 57.3%. Conclusion Hemithoracic radiotherapy following EPP, although associated with significant early toxicity, is well tolerated. Most patients complete the prescribed treatment, and clinically significant late toxicities are rare.